What is web performance? - Barker, Tom, 1977- (O'Reilly Media, 2018)
How fast is your site? Web performance is crucial as your company moves toward digital transformation-not just the actual time it takes your online experience to load, but also the perception of load time for your users and customers. In this article, Comcast's Tom Barker explains how poor or inefficient web performance can affect your entire transformation process, and why you need to move this task to the top of your list.